CURRICULUM PLANNING IN BOARDING SCHOOL TAHFIZIL QUR’AN ISLAMIC CENTER FOUNDATION - Muhammad Fuad Zaini, Mansur Hidayat Pasaribu (CV. Pusdikra Mitra Jaya, 2020)
Research implementation of learning is taught by teachers who are under the responsibility of the parents. The author argues that the implementation of learning in the tahfizil quran pesantren gives birth to many students memorizing the Koran at a young age, it is all inseparable from a good curriculum, which includes careful curriculum planning, and curriculum planning which includes the formulation of tahfiz goals, tahfiz material, and evaluation. tahfiz. Although there are several obstacles, namely teachers who teach tahfiz are not from the teacher faculty. research method used in this research is the case study method. A case study ( Case Study ) is a study conducted in an incentive, detailed and in-depth manner towards an organization, institution or specific phenomenon. According to Nasution, a case study is a form of research that can be carried out on an individual, a group of individuals, a human group (teacher, ethnic group), human environment (village), or social institutions. Result is Curriculum planning at the Islamic boarding school Tahfizil quran foundation is the realization of people who memorize and have the insight of the Qur'an and have a spiritual, intellectual, and moral balance towards a generation that is civilized by the Qur'an, highly committed to actualizing the teachings of the Al-Qur'an. -Qur'an and beneficial to society. Materials for learning at the Islamic Center foundation pesantren are for SD mainimal 5 Juz, while for Madrasah Tsanawiyah for class VII 5 Juz, for grade VII 10 Juz and for grade IX 15 Juz, Madrasah Aliyah 20 to 25 and for Madrasah Tahfizhil Quran are the targets. 30 juz. In the Tahfizil quran Islamic boarding school there are several methods used, namely: the si'maan method (listening to memorization), the quiz method (giving questions), the splicing method, the talaqqi method and the sorongan method. Target achievement of 2 years 30 chapters with the burden of learning 4 hours / day. And the learning schedule, from morning to dawn until 7 o'clock, and the target is 1 to 2 pages per day (10 to 20 days 1 juz, only then 10 days for memorizing muraja'ah. Evaluation of learning in the tahfizhil quran pesantren by looking at the progress of the students' memorization.Implementation of learning is the process of the learning implementation plan (RPP) which includes preliminary activities, core and pentup activities. In this Islamic boarding school specifically for the tahfizil Quran, it does not use money.